Impaired Iron–Sulfur Cluster Synthesis Induces Mitochondrial PARthanatos in Diabetic Cardiomyopathy - Mengyi Wang; Shiwu Zhang; Jinwei Tian; Fan Yang; He Chen; Shuzhi Bai; Jiaxin Kang; Kemiao Pang; Jiayi Huang; Mingjie Dong; Shiyun Dong; Zhen Tian; et al. (Advanced Science)
Abstract Diabetic cardiomyopathy (DCM), a severe complication of diabetes, is characterized by mitochondrial dysfunction, oxidative stress, and DNA damage. Despite its severity, the intrinsic factors governing cardiomyocyte damage in DCM remain unclear. It is hypothesized that impaired iron–sulfur (Fe–S) cluster synthesis plays a crucial role in the pathogenesis of DCM. Reduced S‐sulfhydration of cysteine desulfurase (NFS1) is a novel mechanism that contributes to mitochondrial dysfunction and PARthanatos in DCM. Mechanistically, hydrogen sulfide (H2S) supplementation restores NFS1 S‐sulfhydration at cysteine 383 residue, thereby enhancing Fe–S cluster synthesis, improving mitochondrial function, increasing cardiomyocyte viability, and alleviating cardiac damage. This study provides novel insights into the interplay between Fe–S clusters, mitochondrial dysfunction, and PARthanatos, highlighting a promising therapeutic target for DCM and paving the way for potential clinical interventions to improve patient outcomes.